Bank Access and Cultural Entropy across the Regions of India - Suresh, Govindapuram (REGION, 2026)
Holding a bank account represents access to an important bank service for achieving the formal financial inclusion of an individual. Unfortunately, at present, people living in different regions of India seem to experience a different level of access to this basic bank service and are therefore experiencing different levels of financial market exclusion. This paper studies to what extent social and cultural barriers hinder this effective banking access across the regions of India. Normative caste-based exclusion can be modified by the rigidity of the local context in following inherited norms. This overall cultural rigidity of the context can be termed cultural openness. The Culture Based Development (CBD) approach to quantify cultural openness through the Cultural Entropy measure is employed here. Using data from the National Family Health Survey (NFHS) and National Sample Survey Organization (NSSO), I conduct a probit model estimation to test how Cultural Entropy (CE) modifies the caste discrimination effect in access to bank services. I find that the there is strong evidence that regional Cultural Entropy modifies significantly the individual caste discrimination experience across the regions of the country.